2016
DOI: 10.1111/ans.13804
|View full text |Cite
|
Sign up to set email alerts
|

Potentially preventable deaths in the Victorian Audit of Surgical Mortality

Abstract: Overall assessment of the preventability of death is unique to VASM. This allows an additional level of analysis to be applied to the circumstances surrounding each mortality and correlation of preventability of death with clinical management issues provides important feedback to surgeons and health-care providers to further improve the safety and quality of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
(29 reference statements)
2
7
1
Order By: Relevance
“…The median age in the whole cohort in this study was 82 years, consistent with other Australian surgical mortality audits. 4 Our study revealed a much higher fraction of patients receiving critical care compared to the UK NCEPOD study (83% versus 22%), 12 and somewhat higher than the SNAP-2 EPICCS audit in the UK, Australia and New Zealand. 14 Although ADLs were documented in many cases, functional assessment and anaesthesia risk scores were only documented in 4%.…”
Section: Comparison With Previous Studiescontrasting
confidence: 50%
See 2 more Smart Citations
“…The median age in the whole cohort in this study was 82 years, consistent with other Australian surgical mortality audits. 4 Our study revealed a much higher fraction of patients receiving critical care compared to the UK NCEPOD study (83% versus 22%), 12 and somewhat higher than the SNAP-2 EPICCS audit in the UK, Australia and New Zealand. 14 Although ADLs were documented in many cases, functional assessment and anaesthesia risk scores were only documented in 4%.…”
Section: Comparison With Previous Studiescontrasting
confidence: 50%
“…2 Similarly, the REASON study in Australia (2015) reported a 20% complication rate in surgical patients over 70 years of age, 3 compared with only a 0.3% rate for the overall surgical population. 4…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although our POMR is low, despite many late presentations, the service, for those who can access it, delivers safely. However, we can still learn to improve the safety and quality of service provided by reviewing individual mortalities on a case by case basis and by identifying preventable factors where patients suffer morbidity or mortality 19–21 . The strong public health message, is that surgical, anaesthetic and obstetrics care will save more lives when there is greater access and less delay.…”
Section: Discussionmentioning
confidence: 99%
“…All CMIs are further classified as either preventable or not preventable. 4 The previous study identified that over a two-year period 46 patient deaths from the large health service should have been referred to VASM according to the reporting criteria. The total number of deaths that were reported over the same period was 316 meaning that 12.7% (46/316 + 46) of reportable surgical deaths were not reported.…”
Section: Methodsmentioning
confidence: 99%